2019
DOI: 10.9734/jemt/2019/v24i330165
|View full text |Cite
|
Sign up to set email alerts
|

Online Shopping Industry and Its Consumers in Nigeria

Abstract: Aims: The purpose of this study was to examine online shopping industry and its consumers in Nigeria. Study Design: Quantitative study which adopted a positivistic ontology and descriptive survey design. Place and Duration of Study: The study was carried out between February 2018 and March 2019 among students of six universities in south-south geo-political zone of Nigeria. Methodology: This study adopted stratified random sampling methods to select undergraduate students of six tertiary inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Survey method in the form of Likert scale questionnaire has been widely used in social science research (Nwankwo, Kanyangale, & Abugu, 2019;Olasanmi, 2019;Saeed, 2019). Items of the questionnaire are designed to ask participant about their perception for the different proposed variables, which are five website qualities as antecedent variables, and E-satisfaction as dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Survey method in the form of Likert scale questionnaire has been widely used in social science research (Nwankwo, Kanyangale, & Abugu, 2019;Olasanmi, 2019;Saeed, 2019). Items of the questionnaire are designed to ask participant about their perception for the different proposed variables, which are five website qualities as antecedent variables, and E-satisfaction as dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…The functions and features of many android mobile phones have generated significant alterations in some of the ways people in sub-Sahara West Africa conduct their daily activities (Ajani and Fakunle, 2021b;Cosmas, Nwankwo, Kanyangale and Okechukwu, 2019;Ajani and Fakunle, 2018;Rahman and Zhang, 2017;Omotayo, 2016;Imam-Tamim, Zin and Ibrahim, 2016). For instance, in the early first quarters of the year 2020, the outbreak of Corona Virus Disease of 2019 (otherwise known as COVID-19) that is transmissible through droplets from the infected respiratory organ of the disease carrier has prompted medical experts to recommend avoiding a close gathering of people and maintaining "social distancing"a term that refers to keeping six feet distance between two people to avoid the spread of the disease (Muoghalu and Fakunle, 2021).…”
Section: Ict and Connectivitymentioning
confidence: 99%
“…Technology has generated a number of advantages for the people in the country through online shopping. For instance, reports about online shopping show that online shoppers in the region found it user-friendly and it provides the users the means of making their choices at their convenient time and location (Cosmas et al, 2019). Moreover, Olaoye and Adebayo (2017) found that ICT has enabled the introduction of cashless policy into the country which tends to generate a decrease in the workload of workers that deals with counting banknotes, however, with several challenges in particular, poor network service delivery.…”
Section: E Overview Of Icts Use and Economic Opportunities In Nigeriamentioning
confidence: 99%
“…MM service is a powerful means to delivering savings service to billions of people globally who have a cell phone but do not have the chance of visiting the halls of financial institutions. It has some benefits over conventional banking methods as it breaks down geographic constraints and offers some benefits such as immediacy, security, and efficiency (Nwankwo, Kanyangale and Abugu, 2019). Two institutions, namely, the Central Bank of Nigeria and some universities in Nigeria, are leveraging technology to continue providing services while adhering to social distance requirement to avoid the spread of coronavirus .…”
Section: Introductionmentioning
confidence: 99%